Media in Times of Crisis: A Case Study on the Impact of Media on Societal Awareness During the COVID-19 Pandemic - Ahmed Jawad Kadhim (Medaad)
This paper aims at establishing the importance of media used in creating consciousness within the society during this COVID-19. This study focuses on how information, shared across the social media, news, entertainment and public health nodes or channels, shaped the public’s perception and compliance to the recommended health measures. The study proved the hypothesis that accurate and timely information relayed by the media enhanced the awareness and in return increased the community participation in the preventive measures. Still, the study also discusses emerging issues including misleading information and polarization that erode public credibility. At last, this research confirms the importance of the role generic media strategies play in promoting the public awareness and preparedness in health emergencies.